Architecture education: rubrics in Google Classroom as a tool of improving the assessment and learning - Siddiquee, Tahir Abdul Rahman; Salman, Mohammad; Kunwar, Rajendra Kopil; Abdulla, Amir; Najid, S. V. P.; Abdullah, Fadzidah; Sanusi, Aliyah Nur Zafirah; Hasan, Mohd. Khalid (Springer Nature, 2023)
Blended learning has emerged as a promising approach in architecture education, combining face-to-face instruction with online tools such as Google Classroom, etc. for teaching and learning as well as assessment. The rubrics is a helpful grading tool that the instructors can use to rate the students’ work in a more standardized, transparent, and easy way. The well-designed rubrics can enable the students in recognising their areas of strength and weakness and it will also help them to improve the quality of their work. Although the rubrics have some limitations, several studies show that they can help teachers communicate their expectations more effectively. In this paper, the researchers discussed the effect of using the rubrics in the Google Classroom in architecture education. The rubrics were developed in Google Classroom to evaluate the main task of the subject i.e., assignments for the students of Bachelor of Architecture. The data was collected from the students through a questionnaire that was developed using the web-based Google Forms platform. The marks obtained in the assignments and the data collected through the questionnaire were presented graphically for ease of understanding. Results indicate that rubrics using Google Classroom facilitate a clearer understanding of expectations, promote consistency in grading and feedback, increased transparency, and support student self-assessment and reflection. The integration of rubrics within Google Classroom enhances students’ engagement, motivation, and overall learning experience.